2011
DOI: 10.1371/journal.pntd.0001154
|View full text |Cite
|
Sign up to set email alerts
|

Justified Concern or Exaggerated Fear: The Risk of Anaphylaxis in Percutaneous Treatment of Cystic Echinococcosis—A Systematic Literature Review

Abstract: Percutaneous treatment (PT) emerged in the mid-1980s as an alternative to surgery for selected cases of abdominal cystic echinococcosis (CE). Despite its efficacy and widespread use, the puncture of echinococcal cysts is still far from being universally accepted. One of the main reasons for this reluctance is the perceived risk of anaphylaxis linked to PTs. To quantify the risk of anaphylactic reactions and lethal anaphylaxis with PT, we systematically searched MEDLINE for publications on PT of CE and reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 31 publications
2
73
1
1
Order By: Relevance
“…No anaphylaxis, allergic reactions or death was noted in either group. Although in the past, puncture/aspiration of CE was considered inadvisable owing to a risk of anaphylaxis, a recent study by Neumayr et al 38 reviewing literature on lethal and non-lethal anaphylactic reactions in PT of CE revealed that lethal anaphylaxis as a result of PT is extremely rare and is observed no more frequently than drug-related anaphylactic reactions. In our study, all complications in the surgery group were seen to occur in patients undergoing cystectomy with tube drainage.…”
Section: Discussionmentioning
confidence: 99%
“…No anaphylaxis, allergic reactions or death was noted in either group. Although in the past, puncture/aspiration of CE was considered inadvisable owing to a risk of anaphylaxis, a recent study by Neumayr et al 38 reviewing literature on lethal and non-lethal anaphylactic reactions in PT of CE revealed that lethal anaphylaxis as a result of PT is extremely rare and is observed no more frequently than drug-related anaphylactic reactions. In our study, all complications in the surgery group were seen to occur in patients undergoing cystectomy with tube drainage.…”
Section: Discussionmentioning
confidence: 99%
“…PAIR method presents as excellent diagnostic and therapeutic approach to treatment of hydatid disease. It is relatively safe, rapid and is a powerful tool in resolving hydatid cysts in abdominal cavity (Neumayr et al, 2011). However, it has its limits: superficially situated cysts are not suitable for punction because of the spill risk (Yagci et al, 2005 …”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, infection with three species of tapeworm presents a significant health problem: E. granulosus, with dogs and some other canids as definitive hosts and humans, sheep, goats, cattle, pigs and horses as intermediate hosts and carriers of larval stage (Markell et al, 2000). Other form is alveolar echinococcosis caused by E. multilocularis, with foxes, dogs and catsas definive hosts, small rodents as intermediate hosts and humans as intermediate (accidental) hosts (Dražilová et al, 2012) These two forms are of special importance due to wide distribution and serious medical and economic impact.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that albendazole causes disappearance of lesions in about 48% cases and reduction in the size in about 28% which is well supported by Magnetic resonance studies. 13,14 Surgery remains the mainstay of treatment in intracranial hydatid cyst. Dowling's procedure being most commonly used involves continuous saline irrigation in cyst brain interface causing complete delivery of the cyst without rupture.…”
mentioning
confidence: 99%